A sustainable path towards water purification an insight based on hydrophobic Deep Eutectic Solvents - Florindo, Catarina (2022)
"One of the main concerns of modern society is to provide clean water for everyone. The occurrence of a wide diversity of micropollutants in aquatic ecosystems leads to serious public health and environmental problems. Thus, the development of sustainable and cost-effective alternatives for water purification technologies is nowadays an important challenge. Deep eutectic solvents (DESs) have been proposed as new alternatives to conventional solvents and even ionic liquids. The choice of low cost, naturally occurring compounds and the straightforward preparation are among the key features of these solvents.(...)"